2018
DOI: 10.1111/1440-1630.12522
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of social and community participation of people with non‐traumatic spinal cord injury

Abstract: By using a qualitative approach, this study adds to the understanding of the adjustment process experienced by people following non-traumatic spinal cord injury when they return to living in the community. Although findings parallel those of studies conducted with people with TSCI, there are some differences that may warrant alternative approaches from occupational therapists working with people with NTSCI. Such approaches include assisting people with NTSCI to modify their expectations regarding how they will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…The process of returning to social and community participation was identified as occurring in three main stages: withdrawal; re-emergence into society; and stability. Each stage consisted of adjustment and adaptation in several areas, including the loss of independence; the experience of being out in public; social networks; participation in productivity roles; and expectations regarding satisfactory social and community participation [37].…”
Section: Discussionmentioning
confidence: 99%
“…The process of returning to social and community participation was identified as occurring in three main stages: withdrawal; re-emergence into society; and stability. Each stage consisted of adjustment and adaptation in several areas, including the loss of independence; the experience of being out in public; social networks; participation in productivity roles; and expectations regarding satisfactory social and community participation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Initially after SCI, everyday life drastically changes. Everyday life occupations, roles, and routines are discontinued (5) and the person can experience loss of control and power in relation to their bodies (4,6), and in relations to others (4). Both the situation of being injured and the hospital environment are unfamiliar (4,6,96).…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…possibilities for neuroregeneration, management of acute SCI and associated conditions, as well as prevention and management of secondary complications (1). In addition, this needs to be balanced to physical training (1, 3) practice of new skills, applying skills to real world situations (4), and community participation (5). In this way there are many priorities, both for the person, as well as healthcare staff in the initial rehabilitation process.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, greater perceived environmental barriers (e.g., design of home/community, support at home/community, and transportation) were associated with lower social participation [25][26][27][28]. In a series of qualitative studies, social participation was shown to be impacted by physical and mental health [26][27][28][29], societal attitudes [26][27][28][29], and changes in social networks [26,27]. These factors have also been shown to influence return to work, which is an important marker of a sense of belonging [30].…”
Section: Introductionmentioning
confidence: 99%